Beauty in South Korean TV Drama Series Based on Television Artistic Elements in the Series 'True Beauty’ - Rahmawati, Handini; Suhartami, Wiwik; Irawanto, Budi (Journal of Urban Society's Arts, 2023)
South Korean beauty standards have become increasingly globalized,including in Indonesia, largely through the influence of the South Korean entertainment industry, particularly television drama series and K-pop, commonly referred to as the Hallyu industry. Beauty is frequently constructed as a social issue within South Korean television dramas. One drama series that explicitly addresses this issue is True Beauty, which portrays socially accepted beauty standards and their rolein shaping interpersonal interactions. This study aims to examine the representation of beauty in the South Korean television drama series True Beauty by employing television artistic elements as an analytical framework. The findings reveal how these artistic elements are utilized to construct and communicate beauty ideals within then arrative. Furthermore, the study identifies representations of beauty from the perspectives of supporting characters during social interactions with the main character, who is perceived as unattractive without makeup and attractive with makeup. These interactions produce three dominant perspectives: the meaning ofbeauty, self-perception of beauty, and perceptions of beauty toward others. The influence of True Beauty extends beyond South Korea to Indonesia, where South Korean beauty ideals have increasingly become a reference point, as reflected in the emergence of beauty-related content created by Indonesian beauty vloggers following the series' broadcast.